New synthetic glass-based supplementary cementitious materials derived from basalt composition. (1st April 2022) - Alzeer, Mohammad I.M.; Cheeseman, Christopher; Kinnunen, Paivo
Abstract: The cement industry faces an increasing demand for new supplementary cementitious materials (SCMs) as alternative to slags and ashes, the sources of which are in continuous depletion. This study reports on the characteristics of synthetic aluminosilicate glasses derived from basalt composition (BGs) as new SCMs. The pozzolanic activity of the developed glasses as well as their influence on the hydration kinetics, microstructure, and mechanical properties of blended cements are reported. The obtained results show that pastes containing BGs demonstrated faster hydration rate and higher compressive strength compared to those containing commonly applied granulated blast furnace slag (GBFS). In addition, the developed glasses demonstrated higher pozzolanic activity than GBFS as demonstrated form the measured amount of portlandite and strength activity index. The developed glasses can be obtained from earth abundant carbon-free raw materials as it is similar in composition to basalt. Therefore, this novel approach has potential to provide low-carbon cementitious binders for the concrete industry. Highlights: Synthetic aluminosilicate glass is used as supplementary cementitious materials (SCMs). The developed glass possesses higher pozzolanic reactivity than granulated blast furnace slag. The glass could be synthesised with low-raw materials related CO2 emissions. This novel approach has potential to provide low-carbon cementitious binders.